Fatigue and Sleep Disturbance in Hospitalized Adolescents with Cancer Receiving Chemotherapy - Chookanhom, Phatcharee; Patoomwan, Autchareeya; Pakakasama, Samart (Nursing Research and Innovation Journal, 2021)
This descriptive study aimed to describe fatigue and sleep disturbance in hospitalized adolescents with cancer receiving chemotherapy. The purposive sample included 33 adolescents with cancer admitted to two tertiary hospitals to receive chemotherapy. The instruments were the Fatigue Scale-Adolescent FS-A and Sleep Diaries. Data were analyzed using descriptive statistics. The results of the study revealed that most adolescents reported mild to moderate level of fatigue. The results did not indicate sleep disturbances as obtained from the daily sleep recordings. The average sleep duration was 9.24 hours on the second day of the chemotherapy treatment.The daytime naps were between 31 and 60 minutes per day for all three days, and the time from beginning to sleep (sleep latency) lasted more than 40 minutes. The perceived sleep adequacy were reported as slightly sleepy on the first day and quite drowsy on the third day. The results of this study provide basic information for nurses and other healthcare professionals to beware of fatigue and sleep disturbance in adolescents with cancer receiving chemotherapy and routinely assess these symptoms during children’s hospitalization for planning appropriate interventions. Keywords: Adolescent, Fatigue, Sleep disturbance, Chemotherapy, Hospitalization